MODELLING THE EFFECTS OF LONG-TERM URBAN LAND USE CHANGE ON THE WATER BALANCE - DAGMAR HAASE (Acta Geographica Debrecina. Landscape & Environment Series)
The level of land consumption for housing and transport contrasts sharply with both the necessity and the legal obligation to maintain the ecological potential afforded by open spaces to meet the needs ofcurrent and future generations in terms of resource protection and climate change. Owing to the increasing intensity of soil usage, in many urban landscapes the soil conditions has deteriorated. The natural filter and run-off regulating functions of soils are impaired or even disappeared altogether by land surfacing. Since such soil functions closely depend on the soil’s biophysical properties, thedecline of water balance functionality caused by urbanisation and increasing imperviousness varies. In response to the demand to sustainably secure urban water resources, it needs to be assessed exactly how land surfacing affects the functions concerned. Analysing and evaluating the urban land use change and the respective imperviousness on the long-term water balance ought to improve ourgeneral understanding of the water household related impact of urbanisation. Therefore, the aim of this paper is to assess the impact of urban land use change and land surfacing on the long-term waterbalance over a 130-year trajectory using the example of Leipzig. In particular, attention is to be paid to evapotranspiration, direct runoff and groundwater recharge.